Quantum Theory of Conducting Matter - Fujita, Shigeji (Springer, 2017)
Introduction -- Lattice vibrations and heat capacity -- Free electrons and heat capacity -- Electric conduction and the Hall effect -- Magnetic susceptibility -- Boltzmann equation method -- Bloch theorem -- The Fermi liquid model -- The Fermi surface -- Bloch electron dynamics -- De Haas-Van Alphen oscillations -- Magnetoresistance -- Cyclotron resonance -- Seebeck coefficient (Thermopower) -- Infrared Hall effect.